2009
DOI: 10.1007/s00270-008-9482-6
|View full text |Cite
|
Sign up to set email alerts
|

Early Indicators of Treatment Success After Percutaneous Radiofrequency of Pulmonary Tumors

Abstract: We retrospectively reviewed the imaging of patients after radiofrequency ablation (RFA) of lung metastases performed at our institution to assess the usefulness of ground glass opacification (GGO) margin for the prediction of complete tumor ablation. From January 2004 to March 2007, patients were identified where there was a postprocedure thin collimation scan to allow multiplanar reformatting, either immediately or at 24 h and at least 6 months of imaging follow-up. Thirty-six tumors in 22 patients were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(52 citation statements)
references
References 15 publications
2
50
0
Order By: Relevance
“…Many predictors of tumor response after lung ablation have been proposed. Traditional predictors of local recurrence in PIA include tumor size and ablation margin (28)(29)(30). We saw a significant association between tumor size and local recurrence.…”
Section: Vascular and Interventional Radiologymentioning
confidence: 62%
“…Many predictors of tumor response after lung ablation have been proposed. Traditional predictors of local recurrence in PIA include tumor size and ablation margin (28)(29)(30). We saw a significant association between tumor size and local recurrence.…”
Section: Vascular and Interventional Radiologymentioning
confidence: 62%
“…It is well known that tumours may extend microscopically into the adjacent lung parenchyma by 6-8 mm, and it is therefore suggested that the ablation zone should be at least 1 cm larger than the lesion. 37,40,41 In an article by de Baère et al, 12 the ratio of post-treatment GGO to the pre-treatment tumour area was found to be predictive of success. If the ratio was at least four, the rate of complete ablation at 4 months was found to be 96%.…”
Section: Normal Post-treatment Appearancesmentioning
confidence: 97%
“…Although this can be short lived, it is a useful sign as if it encompasses the lesion with a satisfactory margin, there is good correlation with cell death and thus successful treatment. 12,37 Over a period of a week, the GGO usually changes to more dense airspace opacification. 38 GGO represents a transition from non-viable to viable tissue, and the outer margin of the shadowing probably overestimates the zone of complete ablation by 3-4 mm, emphasizing the need for an adequate treatment margin, analogous to the surgical margin in a resected tumour 39,40 ( Figure 2).…”
Section: Normal Post-treatment Appearancesmentioning
confidence: 99%
“…The tumor tissue is considered to be incorporated in the ablation zone when the GGO completely surrounded the tumor [31,43]. The GGO should encounter the treated tumor with a circumferential margin of at least 5 mm for complete tumor ablation [44]. Other authors recommend that the area of postablation GGO should be 4 times the area of the tumor before ablation.…”
Section: Pretreatment Assessment Procedural Features and Postprocedmentioning
confidence: 99%